1990
DOI: 10.1159/000243203
|View full text |Cite
|
Sign up to set email alerts
|

Total Body Water Measurement in Normal and Diabetic Pregnancy: Evidence for Maternal and Amniotic Fluid Equilibrium

Abstract: The H2[18O] tracer dilution method was applied to quantify total body water in 6 normal nonpregnant women, 8 normal pregnant women (gestation 29.3 ± 6.0 weeks, range 21–37 weeks), and 8 insulin-dependent diabetic pregnant subjects (gestation 29.4 ± 6.1 weeks, range 20–37 weeks). Plateau or equilibrium enrichment of 18O in the breath CO2 was achieved at approximately 2h in nonpregnant normal subjects. In contrast, in pregnant subjects equilibrium plateau was reached l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The subjects ate their last meals at 6:00 p.m. the evening before the day of the study. They were given [ 2 H]water orally (ϳ3 gm/kg of body water), assuming total body water to be 55% of body weight (14), in three divided doses at 11:00 p.m., 3:00 a.m., and 7:00 a.m. Blood samples in heparinized syringes were obtained at frequent intervals starting at 8:00 a.m. and lasting until 12:00 noon.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects ate their last meals at 6:00 p.m. the evening before the day of the study. They were given [ 2 H]water orally (ϳ3 gm/kg of body water), assuming total body water to be 55% of body weight (14), in three divided doses at 11:00 p.m., 3:00 a.m., and 7:00 a.m. Blood samples in heparinized syringes were obtained at frequent intervals starting at 8:00 a.m. and lasting until 12:00 noon.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were instructed not to eat or drink anything after the dose. It has been suggested that full isotopic equilibration with the TBW pool may require up to 4 h or more in late gestation (32). However, in practical terms, a prolonged overnight fast in late gestation is quite difficult, and thus the postdose sample was collected 3 h after 2 H 2 O ingestion as per Lederman et al (17).…”
Section: Tbw By 2 H 2 Omentioning
confidence: 99%
“…Two methods are utilized to determine TBW by dilution: plateau and back extrapolation. With the plateau method, a second physiological sample is obtained after an equilibration period; extended in pregnancy to 4 h for oral dosing and 3 h for subcutaneous dosing to ensure equilibrium, 44 as extracellular water compartments are expanded. With back extrapolation, physiological samples are collected at several intervals up to 14 days after dose administration, and TBW is calculated by back extrapolation to the time of dose.…”
Section: Techniques For Measuring Maternal Body Compositionmentioning
confidence: 99%